2016
DOI: 10.1007/s11238-016-9546-z
|View full text |Cite
|
Sign up to set email alerts
|

Bid pooling in reverse multi-unit Dutch auctions: an experimental investigation

Abstract: In this article we experimentally investigate reverse multi-unit Dutch auctions in which bidders compete to sell their single unit to a buyer who wants to purchase several objects. Our study yields three insights: (i) bids are substantially higher than Nash equilibrium bids predicted by standard economic theory; (ii) these higher-than-predicted prices gradually decline in later periods; and (iii) bid pooling (or simultaneous bidding) is frequently observed-the majority of bidders submit their bids immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…4 (c), the results are identical to the PAB mechanism: both mechanisms are price discriminatory and, under the assumption that all agents follow the same strategy, the result is the same. However, some experimental studies, for example, by Gillen et al [36] showed that due to the specific clearing procedure, the DRA market participants tend to follow the underbidding (UB) strategy, which in this case provides market equilibrium prices which deviate from the true market equilibrium by 1 £/MW/h for the three and six agents scenarios. The results for the Vickery-Clarke-Groves (VCG) auction, presented in Fig.…”
Section: Results Of Step II -Strategic Bidding and Dominant Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…4 (c), the results are identical to the PAB mechanism: both mechanisms are price discriminatory and, under the assumption that all agents follow the same strategy, the result is the same. However, some experimental studies, for example, by Gillen et al [36] showed that due to the specific clearing procedure, the DRA market participants tend to follow the underbidding (UB) strategy, which in this case provides market equilibrium prices which deviate from the true market equilibrium by 1 £/MW/h for the three and six agents scenarios. The results for the Vickery-Clarke-Groves (VCG) auction, presented in Fig.…”
Section: Results Of Step II -Strategic Bidding and Dominant Strategiesmentioning
confidence: 99%
“…In the objective function (34), the first term constitutes the costs for accepted flexible capacity P A with offer price π O = {π O a ∈ R |G| ≥0 }, while the second term limits the acceptance of offers, excluding those whose price exceeds ceiling price π. The first constraint (35) limits accepted capacity P A to the offered capacity P O , while the second constraint (36) establishes that the demand capacity is equal to the accepted capacity plus the unmet demand.…”
Section: Market Clearingmentioning
confidence: 99%
See 3 more Smart Citations